Arbuscular mycorrhiza detoxifying response against arsenic and pathogenic fungus in soybean - Spagnoletti, Federico Nicolás (2016)
Uptake of Arsenic (As) in plant tissues can affect metabolism, causing physiological disorders, even death. As toxicity, but also pathogen infections trigger a generalised stress response called oxidative stress; however knowledge on the response of soybean (Glycine max L.) under multiple stressors is limited so far. Arbuscular mycorrhizal fungi (AMF) enhance the tolerance of host plants to abiotic and biotic stress. Thus, we investigated the effects of the AMF Rhizophagus intraradices on soybean grown in As-contaminated soils as well as in the presence of the pathogen Macrophomina phaseolina (charcoal rot of the stem). Plant parameters and degree of mycorrhizal colonization under the different assessed treatments were analyzed. Content of As in roots and leaves was quantified. Increasing As level in the soil stopped plant growth, but promoted plant As uptake. Inoculation of soybean plants with M. phaseolina accentuated As effect at all physiological levels. In the presence of mycorrhizal symbiosis biomass dramatically increased, and significantly reduced the As concentration in plant tissues. Mycorrhization decreased oxidative damage in the presence of both As and the pathogen. Furthermore, transcription analysis revealed that the high-affinity phosphate transporter from R. intraradices RiPT and the gene encoding a putative arsenic efflux pump RiArsA were up-regulated under higher As doses. These results suggest that R. intraradices is most likely to get involved in the defense response against M. phaseolina, but also in the reduction of arsenate to arsenite as a possible detoxification mechanism in AMF associations in soybean. Capsule abstract: R. intraradices actively participates in the soybean antioxidant defense response against arsenic stress and M. phaseolina infection.